The European Approach to Microcredentials (Revista Electrónica Calidad en la Educación Superior, 2022)
During last years an increasing demand of short learning programs has taken place all over the world in order to reskill and upskill knowledge and professional skills. This education is offered not only by the traditional educational institutions, but also by private undertakings, governmental and non-governmental institutions, professional associations. Even if these programs are broadly accepted, they present different problems, mainly regarding their quality assurance and recognition. European institutions are quite aware of these problems and they have proposed their own solution. In this work we approach the open questions regarding microcredentials and the European approach to solve them.
Keywords: Microcredentials; High Education; Quality Assurance; Recognition of diplomas; Employability; Lifelong learning; Reskilling and Upskilling